Reviewing the Intellectual Structure of the Knowledge Base on Principal Instructional Leadership: An Integrated Bibliometric and Thematic Analysis, 1941-2024 - Gurr, David; Karakose, Turgut; Tulubas, Tijen; Polat, Hakan (Sage Publications Inc, 2025)
This study combines bibliometric performance and thematic analysis of the principal instructional leadership (PIL) research field using SciMAT. The analysis included 695 articles indexed on two reputable databases, Scopus and Web of Science (WoSCC), and offered a comparative and deeper understanding of the thematic evolution of the field across three periods of analysis between 1941 and 2024. The results showed that PIL, which was initially conceptualized as a top-down, directive leadership, evolved into a more indirect and integrated perspective of leadership, albeit maintaining the central role of the principal as the leader of leaders. The knowledge base of PIL evolved in the last 85 years from focusing on the instructional leadership roles of the principals as chief school administrators to the investigation of the roles of principals and teachers and finally to investigations with more integrated perspectives. This evolution parallels the evolution of leadership perspectives and models in the educational field broadly, and the increasing focus on leadership as key to school effectiveness and improvement.
Keywords: Principals; leadership; school/teacher effectiveness; teacher education/development; historical analysis; secondary data analysis; research methodology; principal instructional leadership; instructional leadership; educational leadership; school leadership; SciMAT